Detecting punches from multi-views videos data for performance analysis in elite boxing - Vitel, V.; Talbi, I.; Schortgen, A.; Goyallon, T.; Sauliere, G.; Moussa, I.; Reveret, L.; Brezephin, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The quantification of punches thrown and received by a boxer is a key performance indicator to assess boxing activity [1]. More than a scoring factor, hit quantification allows to evaluate the physical load endured, which is essential for injury prevention [2]. Manually counting punches is a tedious and time-consuming annotation workload. To overcome this challenge, we have developed an automatic method for punch recognition from videos.